Hubungan Indeks Massa Tubuh (IMT) Dengan Daya Tahan Kardiovaskuler Ekstrakurikuler Futsal Putra di SMP Negeri 11 Pontianak - Sari, Juniarti; Effendi, Awang Roni; Sabransyah, Mohammad (Journal Sport Academy, 2023)
The aim is to find the relationship between Body Mass Index and Cardiovascular Endurance for men's futsal extracurricular activities at SMP Negeri 11 Pontianak. The research method used in this research is descriptive method. The data collection technique used is measurement, and the collection tool used is a test. The population in this study were male extracurricular students in grades VII, VIII and IX of SMP Negeri 11 Pontianak, totaling 30 students. The selection of the research sample was carried out by total sampling. The data analysis technique used was two statistical tests, namely Pearson's Spearman rank correlation and regression analysis with a significant level of 5%. The results of the study. The correlation coefficient test was carried out by consulting the price value of r count with the price of r table, at α = 0.000 - 0.199 with N = 30 obtained r table of 0.000 - 0.199. The correlation coefficient rx.y = 0.095, means that the correlation coefficient is very low (not significant). The hypothesis reads "there is no relationship between body mass index and cardiovascular endurance in men's futsal extracurricular activities at SMP Negeri 11 Pontianak." Not accepted with a positive relationship and with a low degree of correlation.